One-Year Comparative Evaluation of Highly Aspherical Lenslets and Horizontally Asymmetric Peripheral Defocus Lenses for Myopia Control in School-Aged Children - Ivana Orešković; Maja Malenica Ravlić; Lana Knežević; Blanka Doko Mandić; Goran Marić; Ante Vukojević; Mia Zorić Geber; Zoran Vatavuk; Ivan Sabol; Jelena Škunca Herman (Life, 2025)
Purpose: The aim of this study was to compare the one-year efficacy of three spectacle lens designs, highly aspherical lenslets (HALs), horizontally asymmetric peripheral defocus (HAPD) lenses, and standard single vision lenses (SVLs) in slowing myopia progression in school-aged children. Methods: In this prospective, non-randomized study, 57 children, aged 8–17 years, were grouped based on the type of lenses worn: HAL (n = 16), HAPD (n = 21), or SVL (n = 20). Comprehensive ophthalmologic examinations were performed at baseline, 6 months, and 12 months. Outcome measures included spherical equivalent refraction (SER), spherical refraction (SR), cylindrical refraction (CR), and axial length (AL). Data were analyzed using non-parametric tests with significance set at p < 0.05. Results: All groups showed some progression in SER and AL over 12 months. The HAL group demonstrated the smallest median SER change (−0.3 D), compared to HAPD (−0.5 D) and SVL (−0.4 D), though group differences were not statistically significant (p = 0.111). Axial elongation was significantly lower in the HAL group (0.1 mm, IQR: 0.0–0.2 mm) compared to HAPD and SVL (both 0.2 mm, p < 0.0001). CR remained stable in all groups, with no clinically meaningful changes. The HAPD groups showed no advantages over SVL in any parameter. Conclusions: Among the three lens types studied, HAL lenses were the most effective in reducing both refractive and axial myopia progression over 12 months. These findings support their use as a reliable intervention in pediatric myopia control.